Envenomation caused by Latrodectus geometricus in São Paulo State, Brazil: A case report - Almeida, Ricardo Augusto Monteiro De Barros [UNESP]; Ferreira, R. S. [UNESP]; Chaves, C. R. [UNESP]; Barraviera, B. [UNESP] (FapUNIFESP (SciELO), 2009)
Widow spiders (Latrodectus spp.), also known as black widows, have a worldwide distribution and can cause latrodectism. To the best of our knowledge, in Brazil, only one case of Latrodectus geometricus (Koch, 1841) envenomation in a human has been reported. The aim of the present report is to describe a spider bite caused by Latrodectus geometricus in a patient who lives in Paranapanema, São Paulo state, Brazil.
Keywords: Brown widow; Envenomation; Latrodectism; Latrodectus geometricus